A New Class of Cure Rate Survival Models: Properties, Inference and Applications - Barriga, Gladys D. C. [UNESP]; Suzuki, Adriano K.; Cancho, Vicente G.; Louzada, Francisco (World Scientific Publ Co Pte Ltd, 2021)
We propose a new class of survival models for time-to-event data with a cure fraction. This new model is an extension of the promotion time cure rate model. Furthermore, we extend the model to the regression model to evaluate the effect of covariates in the cure fraction. An expectation-maximization algorithm is adopted for estimating the model parameters. A simulation study is conducted in order to assess the proposed model and the computation algorithm. The methodology is illustrated using a real Brazilian bank personal loan portfolio data set.
Keywords: Cured fraction; cure rate models; likelihood function; scoring credit; survival models